Structure Design and Composition Engineering of Carbon‐Based Nanomaterials for Lithium Energy Storage - Geng, Hongya; Peng, Yan; Qu, Liangti; Zhang, Haijiao; Wu, Minghong (Advanced energy materials, 2020)
Carbon‐based nanomaterials have significantly pushed the boundary of electrochemical performance of lithium‐based batteries (LBs) thanks to their excellent conductivity, high specific surface area, controllable morphology, and intrinsic stability. Complementary to these inherent properties, various synthetic techniques have been adopted to prepare carbon‐based nanomaterials with diverse structures and different dimensionalities including 1D nanotubes and nanorods, 2D nanosheets and films, and 3D hierarchical architectures, which have been extensively applied as high‐performance electrode materials for energy storage and conversion. The present review aims to outline the structural design and composition engineering of carbon‐based nanomaterials as high‐performance electrodes of LBs including lithium‐ion batteries, lithium–sulfur batteries, and lithium–oxygen batteries. This review mainly focuses on the boosting of electrochemical performance of LBs by rational dimensional design and porous tailoring of advanced carbon‐based nanomaterials. Particular attention is also paid to integrating active materials into the carbon‐based nanomaterials, and the structure–performance relationship is also systematically discussed. The developmental trends and critical challenges in related fields are summarized, which may inspire more ideas for the design of advanced carbon‐based nanostructures with superior properties. Carbon‐based nanomaterials represent cutting‐edge materials in energy storage and conversion fields due to their superior properties. This review summarizes the dimensional design and composition engineering of carbon‐based materials for boosting lithium storage capability, and further discusses their structure–performance relationship. The development trends and critical challenges are also given for the design of advanced carbon‐based electrode materials.